2013
DOI: 10.1016/j.jval.2012.08.2223
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Experimental Designs for Discrete-Choice Experiments: Report of the ISPOR Conjoint Analysis Experimental Design Good Research Practices Task Force

Abstract: Stated-preference methods are a class of evaluation techniques for studying the preferences of patients and other stakeholders. While these methods span a variety of techniques, conjoint-analysis methods-and particularly discrete-choice experiments (DCEs)-have become the most frequently applied approach in health care in recent years. Experimental design is an important stage in the development of such methods, but establishing a consensus on standards is hampered by lack of understanding of available techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
1,254
1
21

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,344 publications
(1,281 citation statements)
references
References 33 publications
5
1,254
1
21
Order By: Relevance
“…The combinations of attributes and levels that defined each treatment pair were determined by an experimental design, which was developed consistent with recent guidance (10). We used the SAS implementation of a commonly used D-optimal algorithm to construct a fractional factorial experimental design (11,12).…”
Section: Methodsmentioning
confidence: 99%
“…The combinations of attributes and levels that defined each treatment pair were determined by an experimental design, which was developed consistent with recent guidance (10). We used the SAS implementation of a commonly used D-optimal algorithm to construct a fractional factorial experimental design (11,12).…”
Section: Methodsmentioning
confidence: 99%
“…4*(3^3)*2) different pharmacy services, in 23,220 different pairs. 37 Experimental design theory was used to select a manageable number of pairs to present to participants, whilst maximising the efficiency (i.e. precision) of the preference estimates elicited from the choices.…”
Section: (I) Identification and Selection Of Attributes And Levelsmentioning
confidence: 99%
“…It is used for a study of reported behaviour [18]. The vignettes are presented in pairs of two to the respondents.…”
Section: Methodsmentioning
confidence: 99%